USULAN PERBAIKAN POSTUR KERJA OPERATOR PROSES PRODUKSI BATIK CAP DI BATIK PUTRI MULYO DENGAN METODE VISUAL MANAGEMENT - Anita Rosifah; Susy Susmartini; Irwan Iftadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
Observations made at work stations of batik cap production, there are still some working conditions that are not appropriate on their worker, one of which is unnatural posture. Unusual work postures that can trigger the occurrence of pain complaints such as musculoskeletal disorders (musculoskeletal disorders). Often unwittingly, batik workers work with positions or postures that have health risks such as musculoskeletal disorders (MSDs). Based on the observation seen that at the work station batik production there are some problems related work methods. Therefore, to improve which work station needs to be repaired, it is necessary to do risk assessment of batik production station work posture using Visual Management approach. The Visual Management approach in this study uses the ergonomic analysis method for the whole body of REBA (Rapid Entire Body Assessment) and OWAS (Ovako Working Posture Analysis System), upper limb RULA (Rapid Upper limb Assessment) and OCRA checklist and by adding some aspects Associated with overload and repetitiveness in the OCRA checklist and OWAS. Based on the assessment of work posture by visual management method, the result of OES value shows 3 processes with OES value ≤ 0.4 with accepted operational status and 2 process with OES value is in the range 0.4 <OES ≤ 0.5, with operational status becomes' necessary further investigation, Changes may be required